Moisture content prediction of rain-exposed wood: Test and evaluation of a simple numerical model for durability applications. (15th February 2016) - Niklewski, J.; Fredriksson, M.; Isaksson, T.
Abstract: Decay prediction models are frequently used to estimate the service life of wooden components. These models require knowledge of how the material climate, i.e. moisture content and material temperature, varies over time. In the present study, the performance of a simple numerical moisture transport model was evaluated for use in decay prediction models. First, a model based on Fick's second law of diffusion was calibrated against laboratory measurements where wooden boards were exposed to artificial rain. Second, the model was tested against field-test measurements on wooden boards exposed outdoors above-ground. The influence of rain was investigated by studying the difference between sheltered and exposed specimens over time. Finally, the model was applied to a number of Swedish climates and two different decay-prediction models were used to evaluate the decay rate. The influence of rain on the moisture content in wooden specimens was reproduced with sufficient accuracy for decay prediction. The error between the numerical result and the measurements tended to increase at high moisture contents and with decreasing temperature. However, the total error was reduced when the moisture content history was post-processed in a decay-prediction model as the rate of decay tends to decrease with decreasing temperature. The estimated service life varied with depth and the different decay models. Highlights: A moisture content prediction model for rain-exposed wood was evaluated. Laboratory and field moisture content measurements were used for evaluation. The model reproduces the measurements with sufficient accuracy for the application. Moisture distribution is important when predicting decay risk in rain-exposed wood. The decay risk varies with depth and geographic location.